Korelasi antara Literasi Bahasa Indonesia dan Literasi Numerasi Matematika Siswa dalam Menyelesaikan Soal Matematika - Aziz, Saddam Al; Septriyanti, Yesi (Lattice Journal : Journal of Mathematics Education and Applied, 2023)
This research includes ex post facto correlation research, which aims to determine the correlation of the independent (free) variable, namely Indonesian Language Literacy (X), with the dependent variable (tied), namely Mathematical Numerical Literacy (Y). The research was conducted in the January-June 2023 semester in 1 class VIII containing 30 students at a junior high school in Padang. Data was collected by testing one-story test questions. The sampling technique is purposive sampling. Data were analyzed using the Spearman Rank Correlation using the Kolmogorov-Smirnov normality test and hypothesis testing. The correlation coefficient value of Indonesian language literacy with the mathematical numeracy literacy variable is "positive 0.953". So that the relationship/correlation of the two variables is categorized as significant, vital, and in the same direction, this can be interpreted that if the Indonesian language literacy of class VIII students in the sample increases, the numeracy literacy of students in solving math problems will also increase, and vice versa.Â Penelitian ini termasuk penelitian korelasi expost facto yang bertujuan mengetahui korelasi Â variabel independen (bebas) yaitu Literasi Bahasa Indonesia (X) dengan variabel dependen (terikat) yaitu Literasi Numerasi Matematika (Y). Penelitian dilakukan semester Januari-Juni 2023 pada 1 kelas VIII berisi 30 siswa pada suatu SMP di kota Padang. Dikumpulkan data dengan mengujikan 1 soal tes cerita. Teknik pengambilan sampelnya purposive sampling. Data dianalisis dengan uji normalitas Kolmogorov Smirnov dan uji hipotesis menggunakan Korelasi Spearman Rank. Nilai koefisien korelasi literasi bahasa Indonesia dengan variabel literasi numerasi matematika bernilai â€œpositif 0,953â€. Sehingga hubungan/korelasi kedua variabel tersebut dikategorikan signifikan, kuat, dan searah. Hal ini dapat diartikan bahwa jika literasi bahasa Indonesia siswa kelas VIII pada sampel semakin meningkat maka literasi numerasi matematika siswa dalam menyelesaikan soal matematika juga akan semakin meningkat, begitu pula sebaliknya.Â